An Analysis of Deixis in the Chernobyl Movie Series - Husni Pratama Noviansyah; Agus Wardhono; K.J. Vargheese (Language Center of Islamic Institute of Uluwiyah (IAI Uluwiyah) Mojokerto Indonesia, 2022)
Language is the most important aspect to support humans in communicating. In communication, people need to understand the meaning of language. Language and context are two inseparable things. In a given context, it is important for listeners or recipients to understand what the speaker meant to say or express. Deixis shows a phenomenon that requires contextual information to understand the meaning of certain words or phrases in their pronunciation. Deixis can be found not only in daily conversations, but also in speeches, films, songs, novels, and the like. This research focuses on deixis in the film Chernobyl in characters that play an important role in the course of the story. The purpose of this study is to find out kinds of deixis that are found in the movie script and to determine the dominant types of deixis. The researchers use descriptive qualitative methods to collect data and have been assisted byAtlas.ti software in data coding. The theory of Levinson is used by the researchers to analyze the type of deixis. In this study, the most dominant deixis is the person deixis (450), the second dominant deixis is place deixis (57), and the third is time deixis (48), followed by discourse deixis (36), and the last is social deixis (26).